Cystic bone tumors of the foot and ankle. Issue 8 (3rd May 2018) - Reda, Bashar
Abstract : Bone tumors are relatively rare in the foot and ankle region. Many of them present as cystic lesions on plain films. Due to the relative rarity of these lesions and the complex anatomy of the foot and ankle region, identification of such lesions is often delayed or they get misdiagnosed and mismanaged. This review discusses the most common cystic tumors of the foot and ankle including their radiographic features and principles of management.